Robustness of Interdependent Networks with Weak Dependency Based on Bond Percolation - Yingjie Qiang; Xueming Liu; Linqiang Pan (Entropy, 2022)
Real-world systems interact with one another via dependency connectivities. Dependency connectivities make systems less robust because failures may spread iteratively among systems via dependency links. Most previous studies have assumed that two nodes connected by a dependency link are strongly dependent on each other; that is, if one node fails, its dependent partner would also immediately fail. However, in many real scenarios, nodes from different networks may be weakly dependent, and links may fail instead of nodes. How interdependent networks with weak dependency react to link failures remains unknown. In this paper, we build a model of fully interdependent networks with weak dependency and define a parameter <semantics>α</semantics> in order to describe the node-coupling strength. If a node fails, its dependent partner has a probability of failing of <semantics>1−α</semantics>. Then, we develop an analytical tool for analyzing the robustness of interdependent networks with weak dependency under link failures, with which we can accurately predict the system robustness when <semantics>1−p</semantics> fractions of links are randomly removed. We find that as the node coupling strength increases, interdependent networks show a discontinuous phase transition when <semantics>α<αc</semantics> and a continuous phase transition when <semantics>α>αc</semantics>. Compared to site percolation with nodes being attacked, the crossover points <semantics>αc</semantics> are larger in the bond percolation with links being attacked. This finding can give us some suggestions for designing and protecting systems in which link failures can happen.